An ethnopharmacological survey and in vitro confirmation of the ethnopharmacological use of medicinal plants as anthelmintic remedies in the Ashanti region, in the central part of Ghana - Agyare, C.; Spiegler, V.; Sarkodie, H.; Asase, A.; Liebau, E.; Hensel, A. (Journal of Ethnopharmacology, 2014)
Ethnopharmacological relevance Infections with helminths are still a big problem in many parts of the world. The majority of the people in West Africa treat such infections with medicinal plants related to the local traditional medicine. The present study aims at identifying medicinal plants traditionally used for worm infections in the Ashanti region, Ghana. In vitro screening of selected extracts from plants on which scientific knowledge is limited was to be performed.Materials and methods Validated questionnaires were administered to 50 traditional healers in the Ashanti region, Ghana. Interviews and structured conversations were used to obtain relevant information. Quantitative and qualitative evaluation was performed additionally to structured cross-referencing of the data using SciFinder® data base. Selected plant species were used for in vitro testing on anthelmintic activity against the free-living model nematode Caenorhabditis elegans.Results 35 plant species were recorded for the use in humans and 6 for the use in animals. Plant material most frequently used were the seeds from Carica papaya, mentioned by nearly all healers. The plausibility of most plants used for treatment of infections with helminths was given in most cases by documentation of potential anthelmintic activity in recent scientific literature. 9 species from plants not or scarcely described in literature for this indication were investigated on in vitro activity. A hydroethanolic (1:1) extract of Combretum mucronatum was most active with a survival rate of nematodes of 89% at 0.1 mg/mL and 58% at 1 mg/mL respectively (levamisole 16%). Extracts of Paullinia pinnata and Phyllanthus urinaria were also assessed to exhibit a minor (85% and 89% respectively at 1 mg/mL), but still significant activity.Conclusion Traditional use of anthelmintic plants from Ghana can be well rationalized by cross-referencing with published literature and phytochemical/pharmacological plausibility.The in vitro investigations of extracts from Combretum mucronatum, Paullinia pinnata and Phyllanthus urinaria exhibited significant effects against nematodes. The anthelmintic activity of these plants should be investigated in detail for pinpointing the respective lead structures responsible for the activity. © 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Anthelmintic; Caenorhabditis elegans; Combretum mucronatum; Paullinia pinnata; Phyllanthusurinaria